Pengaruh Karakteristik Nasabah, Pengetahuan Nasabah, Kualitas Pelayanan Terhadap Keputusan Menggunakan Jasa Perbankan Syariah (Studi Pada Bank Kalsel Syariah Banjarmasin) - Darmadiansyah Darmadiansyah; Emy Rahmawati; Noor Hidayati (Universitas Lambung Mangkurat, 2019)
The test results prove partially the characteristics of the customer (X1), and the quality of service (X3), affecting the decision to use Islamic banking services (Y), while customer knowledge (X2), no partial effect on the decision to use the services of sharia banks in Bank Kalsel Syariah Banjarmasin. Characteristics of customers (X1) is a variable that gives the dominant contribution to the decision to use sharia banking services with a contribution of 35.9%. While simultaneously shows the influence of significant variables Customer characteristics, knowledge of customers, quality of service to the decision process using the services of sharia banking. This is evidenced by the value of Adjusted R Square regression model of 0.246 which means that the dependent variable is influenced by the independent variable of 24.6%. And the rest of 75,4% influenced by other variable not mentioned in this research. Keywords: Characteristics, Knowledge, Service Quality and Decision Using bank services